Glia Regulate the Development, Function, and Plasticity of the Visual System From Retina to Cortex - Benfey, Nicholas; Foubert, David; Ruthazer, Edward S. (Frontiers in Neural Circuits, 2022)
Visual experience is mediated through a relay of finely-tuned neural circuits extending from the retina, to retinorecipient nuclei in the midbrain and thalamus, to the cortex which work together to translate light information entering our eyes into a complex and dynamic spatio-temporal representation of the world. While the experience-dependent developmental refinement and mature function of neurons in each major stage of the vertebrate visual system have been extensively characterized, the contributions of the glial cells populating each region are comparatively understudied despite important findings demonstrating that they mediate crucial processes related to the development, function, and plasticity of the system. In this article we review the mechanisms for neuron-glia communication throughout the vertebrate visual system, as well as functional roles attributed to astrocytes and microglia in visual system development and processing. We will also discuss important aspects of glial function that remain unclear, integrating the knowns and unknowns about glia in the visual system to advance new hypotheses to guide future experimental work.